Acute Alcohol Intoxication Modulates Monocyte Subsets and Their Functions in a Time-Dependent Manner in Healthy Volunteers - Janicova, Andrea; Haag, Florian; Xu, Baolin; Garza, Alejandra P.; Dunay, Ildiko Rita; Neunaber, Claudia; Nowak, Aleksander J.; Cavalli, Paola; Marzi, Ingo; Sturm, Ramona; Relja, Borna (Frontiers in Immunology, 2021)
Background: Excessive alcohol intake is associated with adverse immune response-related effects, however, acute and chronic abuse differently modulate monocyte activation. In this study, we have evaluated the phenotypic and functional changes of monocytes in acutely intoxicated healthy volunteers (HV). Methods: Twenty-two HV consumed individually adjusted amounts of alcoholic beverages until reaching a blood alcohol level of 1‰ after 4h (T4). Peripheral blood was withdrawn before and 2h (T2), 4h (T4), 6h (T6), 24h (T24), and 48h (T48) after starting the experiment and stained for CD14, CD16 and TLR4. CD14brightCD16-, CD14brightCD16+ and CD14dimCD16+ monocyte subsets and their TLR4 expression were analyzed by flow cytometry. Inflammasome activation via caspase-1 in CD14+ monocytes was measured upon an ex vivo in vitro LPS stimulation. Systemic IL-1β and adhesion capacity of isolated CD14+ monocytes upon LPS stimulation were evaluated. Results: The percentage of CD14+ monocyte did not change following alcohol intoxication, whereas CD14brightCD16- monocyte subset significantly increased at T2 and T24, CD14brightCD16+ at T2, T4 and T6 and CD14dimCD16+ at T4 and T6. The relative fraction of TLR4 expressing CD14+ monocytes as well as the density of TLR4 surface presentation increased at T2 and decreased at T48 significantly. TLR4+CD14+ monocytes were significantly enhanced in all subsets at T2. TLR4 expression significantly decreased in CD14brightCD16- at T48, in CD14brightCD16+ at T24 and T48, increased in CD14dimCD16+ at T2. IL-1β release upon LPS stimulation decreased at T48, correlating with TLR4 receptor expression. Alcohol downregulated inflammasome activation following ex vivo in vitro stimulation with LPS between T2 and T48 vs. T0. The adhesion capacity of CD14+ monocytes decreased from T2 with significance at T4, T6 and T48. Following LPS administration, a significant reduction of adhesion was observed at T4 and T6. Conclusions: Alcohol intoxication immediately redistributes monocyte subsets toward the pro-inflammatory phenotype with their subsequent differentiation into the anti-inflammatory phenotype. This is paralleled by a significant functional depression, suggesting an alcohol-induced time-dependent hyporesponsiveness of monocytes to pathogenic triggers.